Airway Analysis in Apert Syndrome. Issue 3 (September 2019) - Forte, Antonio J.; Lu, Xiaona; Hashim, Peter W.; Steinbacher, Derek M.; Alperovich, Michael; Persing, John A.; Alonso, Nivaldo
Abstract : Background: Apert syndrome is frequently combined with respiratory insufficiency, because of the midfacial deformity which, in turn, is influenced by the malformation of the skull base. Respiratory impairment resulting from Apert syndrome is caused by multilevel limitations in airway space. Therefore, this study evaluated the segmented nasopharyngeal and laryngopharyngeal anatomy to clarify subcranial anatomy in children with Apert syndrome and its relevance to clinical management. Methods: Twenty-seven patients (Apert syndrome, n = 10; control, n = 17) were included. All of the computed tomographic scans were obtained from the patients preoperatively, and no patient had confounding disease comorbidity. Computed tomographic scans were analyzed using Surgicase CMF. Craniometric data relating to the midface, airway, and subcranial structures were collected. Statistical significance was determined using t test analysis. Results: Although all of the nasal measurements were consistent with those of the controls, the nasion-to–posterior nasal spine, sphenethmoid-to–posterior nasal spine, sella-to–posterior nasal spine, and basion-to–posterior nasal spine distances were decreased 20 ( p < 0.001), 23 ( p = 0.001), 29 ( p < 0.001), and 22 percent ( p < 0.001), respectively. The distance between bilateral gonions and condylions was decreased 17 ( p = 0.017) and 18 percent ( p = 0.004), respectively. The pharyngeal airway volume was reduced by 40 percent ( p = 0.01). Conclusion: The airway compromise seen in patients with Apert syndrome is attributable more to the pharyngeal region than to the nasal cavity, with a gradually worsening trend from the anterior to the posterior airway, resulting in a significantly reduced volume in the hypopharynx.